Penerimaan Anak Berkebutuhan Khusus di Sekolah Inklusi: Menumbuhkan Inklusi dan Kesetaraan Pendidikan - Zulfitrah .; A. Sri Wahyuni Asti (PREDESTINATION: Journal of Society and Culture, 2023)
Abstract: Inclusive education has been a topic of discussion in the field of education for several decades. The idea of providing an educational environment that accommodates children with special needs has gained traction worldwide. This study aims to investigate the acceptance of students with special needs in inclusive schools. A quantitative research approach was used, and the data were collected through a questionnaire distributed to teachers and students with special needs in inclusive schools. The results indicated that the majority of the children with special needs reported a high level of acceptance in inclusive schools. The analysis also revealed that students with special needs who received support from their teachers and peers reported higher levels of acceptance. These findings suggest that inclusive schools can provide a positive educational environment for children with special needs, and support from teachers and peers is crucial to their acceptance.